'This ward has no ears': Role of the pastoral care practitioner in the hospital ward. Issue 2 (3rd April 2022) - Best, Megan; Washington, Jennifer; Condello, Maria; Kearney, Matthew
Abstract: National Guidelines for Spiritual Care in Australia recommend incorporation of spiritual care in multidisciplinary patient care planning, however it is not known how consistently this is done. A qualitative interview study was designed to explore the practices of pastoral care practitioners in two city hospitals in Australia. Fourteen pastoral care practitioners participated (100% response rate). Interviews were taped and transcribed verbatim. Transcripts were analysed according to thematic analysis. Six themes were identified in the data. These were: (1) a vocation, (2) the role of pastoral care, (3) documentation, (4) communication with other ward staff, (5) barriers to communication, and (6) official recognition of pastoral care workers. While pastoral care workers are convinced of the importance of their work, they experience challenges in expressing this to their colleagues, which may reduce their impact on patient care. Ongoing professionalization of pastoral care will help to reduce this discrepancy.